Genes Underlying Reproductive Division of Labor in Termites, with Comparisons to Social Hymenoptera - Korb, Judith (Frontiers in Ecology and Evolution, 2016)
All social insects are characterized by a reproductive division of labor. Within a colony only a few individuals reproduce (queens and in termites, also a king) while the large majority (workers and soldiers) forgo reproduction, at least temporarily. The evolution of such reproductive altruism can ultimately be explained by inclusive fitness theory. Here, I will review the proximate genetic mechanisms underlying this altruism in termites. As social cockroaches they evolved eusociality independently from the social Hymenoptera, which makes them interesting test cases to look for common underlying mechanisms of eusociality and lineage specific idiosyncrasies. First, I will provide a summary of the genes and their function that have been identified to underlie reproductive division of labor—so called “queen genes,”—in the drywood termite Cryptotermes secundus, an emerging model to study termite social evolution. Second, I outline how widespread these queen genes are across the termite phylogeny, using also evidence from recent genome analyses. I will provide hypotheses about the evolutionary origin of these queen genes, aiming to link proximate mechanisms with ultimate functions. Finally, I will draw comparisons to social Hymenoptera to indicate potential common underpinnings that warrant further testing.